Antioxidant Activity and Lipid Content of Aurantiochytrium sp. from Raja Ampat and Kepulauan Seribu - Witasari, Hardi Astuti; Kintoko, Kintoko; Mahfudh, Nurkhasanah; Suhendra, Suhendra; Rangkuti, Ahmad Faizal; Ilmia, Nisrien; Santoso, Blegoh Iwan; Hutari, Andri (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2025)
Raja Ampat (Southwest Papua Province) and Kepulauan Seribu (Jakarta Raya Province) are part of Indonesia#39;s territory, which includes the mangrove forest area. This habitat supports a diverse array of animals, plants, and microalgae, including Aurantiochytrium sp. It has antioxidant activity related to lipid content. This study aims to identify the lipid content and the antioxidant effects of the microalgae Aurantiochytrium sp.’s extract isolated from the mangrove forest areas of Raja Ampat and Kepulauan Seribu. The extraction process was conducted using the Folch method, which involves a 2:1 (v/v) chloroform-methanol solvent ratio. The microalgae Aurantiochytrium sp. extract of Raja Ampat (MAERA) and microalgae Aurantiochytrium sp. extract of Kepulauan Seribu (MAEKS) were analyzed using GC-MS, antioxidant potential tested in silico by target proteins (5ZLG, 2A1X, 3VLN, and 1EEM) using Autodock Tools, and in vitro by DPPH and ABTS radicals and the carotenoid bleaching method. The results showed that total squalene and fatty acids in MAERA and MAEKS were at different levels. Squalene as a ligand had the lowest binding energy (-9.4, -6.6, -7.7, and -6.5) compared to the native ligand (-5.6, -4.4, -5.2, and -5.2) and ascorbic acid (-5.6, -4.8, -5.3, and -4.9) by in silico antioxidant activity. The in vitro antioxidant activities by DPPH, ABTS, and ß-caroteen bleaching were 103.00 ± 3.75, 216.39 ± 367, 214.62 ± 7,07 (MAERA); and 131.85 ± 23.48, 225.50 ± 3.36, 251.69 ± 5.39 (MAEKS) were not significantly different (pgt;0.05) by all methods. These findings showed that the Aurantiochytrium sp. strains Raja Ampat and Kepulauan Seribu contained diverse levels of fatty acids and squalene. In the in silico study, squalene was evaluated and in vitro, the MAERA and MAEKS extracts showed moderate antioxidant activity.